DEVELOPMENT OF AN RPG MAKER MV-BASED INTERACTIVE GAME AS LEARNING MEDIA ON VIRUS MATERIALS FOR GRADE X STUDENTS AT NURUL ISLAM JEMBER SENIOR HIGH SCHOOL - Nasution, Nanda Eska Anugrah; Yasin, Ridwan; Rizka, Chairany (Jurnal Pendidikan Matematika dan IPA, 2024)
The limited accessibility of digital educational game resources on the topic of viruses in the public domain poses a significant challenge that must be addressed. The primary objective of this research is to determine the validity of the RPG maker MV based game, followed by an assessment of its practicality. The research used Lee Owens as the development model. The result of this study is the produced RPG maker MV-based game, focused on virus material. The validity of the game has been confirmed through product validation conducted by experts in the discipline, achieving an average percentage of 96.63% (highly valid) from material experts, 93.07% (highly valid) from media experts, and 80.71% (valid) from biology teacher practitioners. The practicality of the RPG maker MV-based game was then demonstrated by small-scale trials, yielding an average performance rate of 93% (an exceedingly captivating product), and large-scale trials, yielding an average performance rate of 94.3% (an exceedingly captivating product).